2018
DOI: 10.1038/s42003-018-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

Motion changes response balance between ON and OFF visual pathways

Abstract: Humans are faster at detecting dark than light stationary stimuli, a temporal difference that originates early in the visual pathway. Here we show that this difference reverses when stimuli move, making detection faster for moving lights than darks. Human subjects judged the direction of moving edges and bars, and made faster and more accurate responses for light than for dark stimuli. This light/dark asymmetry is greatest at low speeds and disappears at high speeds. In parallel experiments, we recorded respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…stimuli (Luo-Li et al, 2018), and human visual acuity can be preserved in the absence of ON pathway (Dryja et al, 2005). Moreover, genetic defects of the ON pathway can cause nystagmus in humans (Dryja et al, 2005), which is a deficit in retinal image stabilization.…”
Section: On and Off Functional Specialization In Different Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…stimuli (Luo-Li et al, 2018), and human visual acuity can be preserved in the absence of ON pathway (Dryja et al, 2005). Moreover, genetic defects of the ON pathway can cause nystagmus in humans (Dryja et al, 2005), which is a deficit in retinal image stabilization.…”
Section: On and Off Functional Specialization In Different Speciesmentioning
confidence: 99%
“…Several lines of evidence indicate that ON cortical responses may play an important role in signaling slow motion in visual scenes. Flies rely on the ON pathway to detect slow image motion (Leonhardt et al, 2016), and humans are more accurate at detecting light than dark slow-moving bars (Luo-Li et al, 2018). In rodents and lagomorphs, direction-selective ON retinal ganglion cells show a preference for slow velocities (Oyster, 1968;Sun et al, 2015), and, without the ON pathway, zebrafish lose the optokinetic reflex triggered by slow directional motion (Emran et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that the cortical segregation of ON and OFF pathways may be as pronounced as the segregation for contralateral/ipsilateral eyes or magnocellular/parvocellular pathways (Jin et al, 2011a;Kremkow et al, 2016;Lee et al, 2016). Recent work is also revealing pronounced functional differences between ON and OFF cortical pathways, with low spatial frequencies, optical blur and low light making vision more OFF dominated (Onat et al, 2011;Kremkow et al, 2014;Pons et al, 2017;Jansen et al, 2019) and slow motion making vision and cortical responses more ON dominated (Luo-Li et al, 2018;Mazade et al, 2019). Therefore, our results may inspire a new generation of amblyopia treatments that can take advantage of the different ON and OFF stimulus preferences to selectively strengthen a weak ON cortical pathway.…”
Section: Future Amblyopia Treatmentsmentioning
confidence: 99%
“…The low-level neuronal mechanisms and structures of motion detectors that can detect both these types of motions, have been the focus of numerous studies (Salazar-Gatzimas et al 2018;Clark et al 2011;Tuthill, Chiappe, and Reiser 2011;Theobald 2018;Luo-Li et al 2018;Mo and Koch 2003;Leonhardt et al 2017;Yang and Clandinin 2018). The pioneer motion study of Hassenstein and Reichardt (Von Hassenstein and Reichardt 1956), which used insects and has also been adapted to other animals, suggested a simple computational model (Alexander Borst 2000), the Hassenstein and Reichard Correlator (HRC), based on a delay and correlation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The two types of stimuli (dark and light bars) are presented on a gray background (Fig 2), and are detected through a matrix of On and Off center-surround receptive fields. These receptive fields map the neuronal net and contain a complete overlap of the On-and the Off receptive fields, at the locations of the left and right "motion" directions,Fig 1.For the sake of simplifying the computations of the receptive field matrix and the center-surround receptive fields in the fly's optic lobe, we only subtracted the background (which is used as the surround region) from each pixel (which is used as the center)(Freifeld et al 2013).Note that in accordance with reports on the pathways in the visual system of flies(Alexander Borst and Helmstaedter 2015) and previous computational studies(Salazar-Gatzimas et al 2018;Clark et al 2011;Tuthill, Chiappe, and Reiser 2011;Theobald 2018;Luo-Li et al 2018;Mo and Koch 2003;Leonhardt et al 2017;Yang and Clandinin 2018), we considered only the simple case of two directions of motion although the visual system of flies can sense four directions of motion in the Labula visual layer (Alexander Borst and Helmstaedter 2015).The model simulations indicated that a phi motion with a light stimulus,Fig 2(a-b)caused the On DS cells to provide a significant response, while a phi motion with a dark stimulus,Fig 2 (c-d)…”
mentioning
confidence: 98%